Adoption of improved seeds, evidence from DRC - Bernard, Tanguy; Lambert, Sylvie; Macours, Karen; Vinez, Margaux (HAL, 2019)
Agricultural input subsidies are often considered key instruments to increase adoption of new technologies in developing countries. Using unique experimental data from Equateur province in DRC, we document the effectiveness of such interventions in increasing households adoption of modern seed varieties (MVs). High subsidy levels increase adoption, in particular when other access constraints were also relieved. Demand is highly price sensitive, but demand curves do not display strong discontinuity at low prices. We find very limited spillover effects on adoption by non-voucher recipients. Adoption persists to some extent in the season that follows voucher distribution.